Tatwir al-Wasail at-Ta'limiyah "al-Muhadatsah bi al-Lughah al-Arabiyah" bi al-I'timad 'ala Tathbiq Canva - Abdullah, Maulidati; Firdaus, Muhammad; Chasani, Muchamad Toif (Jurnal Al-Mashadir: Journal of Arabic Education and Literature, 2024)
The aim of this research is to see the feasibility of Arabic muhadasah learning media in terms of material and media. The method used in this research is RnD with a four-D (4-D) approach model developed by Thiagarajan. This 4-D model consists of 4 stages, namely: define, design, development and dissemination. The data collection instrument in this research was a media expert and material expert validation sheet. Arabic Teacher Response Assessment Questionnaire and Student Response Assessment Questionnaire. the validation results from material experts show an average score of 0.95, as well as the media expert validation results show the same average score, namely 0.95, the average results from assessing student responses are 0.93 and the average results from the responses of Arabic language lecturers and Arabic language teachers is 0.91. The findings of this research indicate that Canva-based muhadasah learning media is very suitable as an Arabic language learning media.